Formulation and Clients’ Agency in Cognitive Behavioral Therapy - Yao, Xueli; Dong, Boyu; Ji, Weining (Frontiers in Psychology, 2022)
The experience of loss of agency is one of the reasons for clients to go for psychotherapy. Enhancing clients’ agency has been considered a fundamental factor for successful treatment in psychiatry and psychotherapy, yet few studies have investigated the interactional realization of how therapists do this in authentic psychotherapeutic encounters. Drawing on audio-recorded talk-in-interaction between clients and psychotherapists in cognitive behavioral therapy (CBT) encounters at a mental health center in China, the present paper uses the method of conversation analysis to demonstrate how therapists ascribe agency positions to clients by issuing formulations of what the clients have just said. Two types of formulation were identified: affirmative formulations and challenging formulations. In the first, the therapists highlight the positive aspect of clients’ description of their experiences and ascribe an agentic position to the clients. In the second, the therapists challenge the clients’ implausible views and their non-agentic positioning of themselves. This study shows that therapists’ formulation could be employed to manage the epistemic difficulties associated with claiming knowledge about the clients’ inner states and assessing their feelings. In this sense, formulation is a robust interactional device in negotiating epistemic problems in addressing clients’ experiences and promoting their agency in therapy. However, it is noteworthy that in challenging formulation, therapists claim privileged access to the clients’ knowledge domain and challenge their prior epistemic status, which might run the risk of engendering clients’ resistance.